Sustainability trade theory: institutional pathways to export growth in Sub-Saharan Africa - Dare John Olateju (International Journal of Business Studies, 2026)
Trade openness is widely regarded as a driver of economic growth, yet its contribution to sustainable development in resource-dependent, climate-vulnerable economies remains ambiguous. In Sub-Saharan Africa (SSA), increased trade integration often coincides with environmental degradation, volatile exports, and weak value creation, highlighting a gap in conventional trade–environment frameworks. This study introduces Sustainability Trade Theory (STT), a novel institutional framework that explicates how environmental sustainability, trade openness, and institutional quality interact to shape long-term export performance. STT identifies three key mechanisms: the green competitiveness mechanism, whereby environmentally efficient firms gain latent export advantages; the policy amplification mechanism, in which institutions translate these latent advantages into realized trade outcomes; and the resilience-to-volatility mechanism, which stabilizes export performance against climatic and market shocks. Using SSA economies as the empirical context, STT generates testable hypotheses linking carbon and energy intensity, forest preservation, sustainability ratings, and trade openness to export value. The theory further highlights feedback loops, including a degradation-trap, through which environmental neglect undermines institutional capacity and export growth. By integrating ecological constraints, institutional endogeneity, and trade dynamics, STT provides a unified explanation for divergent export outcomes and offers actionable insights for policymakers seeking to convert trade liberalization into sustainable, resilient growth. The findings underscore that trade openness alone is insufficient; strategic, sustainability-oriented institutional interventions are essential to achieving environmentally responsible export-led development in SSA.